Nanotransfersomes-loaded thermosensitive in situ gel as a rectal delivery system of tizanidine HCl: preparation, in vitro and in vivo performance - Fatma A. Moawad; Adel A. Ali; Heba F. Salem (Taylor & Francis Group, 2017)
The purpose of the current study was to develop tizanidine HCl (TIZ; a myotonolytic agent used for treatment of spasticity) loaded nanotransfersomes intended for rectal administration, aiming to bypass the hepatic first-pass metabolism. TIZ-loaded nanotransfersomes were prepared by thin-film hydration method followed by characterization for various parameters including entrapment efficiency, vesicle diameter, in vitro release and ex vivo permeation studies. Transfersomal formulation composed of phosphatidylcholine and Tween 80 at a weight ratio of (85:15) gave a satisfactory results. It exhibited encapsulation efficiency of 52.39%, mean diameter of 150.33 nm, controlled drug release over 8 h and good permeation characteristics. Optimum formula was then incorporated into Pluronic-based thermoreversible gel using hydroxypropyl methylcellulose (HPMC) as a mucoadhesive polymer. Pharmacokinetic study was performed by rectal administration of transfersomes-loaded in situ gel to rabbits and compared with oral drug solution and rectal TIZ in situ gel. The pharmacokinetic study revealed that the transfersomal formulation successively enhanced the bioavailability of TIZ by about 2.18-fold and increased t1/2 to about 10 h as compared to oral solution. It can be concluded that encapsulation of TIZ into nanotransfersomes can achieve a dual purpose of prolonged TIZ release and enhanced bioavailability and so may be considered as a promising drug delivery system for the treatment of spasticity.